Prevention of bone loss and vertebral fractures in patients with chronic epilepsy—Antiepileptic drug and osteoporosis prevention trial. Issue 11 (6th September 2013) - Lazzari, Antonio A.; Dussault, Philip M.; Thakore‐James, Manisha; Gagnon, David; Baker, Errol; Davis, Samuel A.; Houranieh, Antoun M.
Summary: Purpose: To evaluate whether use of a bisphosphonate (risedronate) in addition to calcium and vitamin D in male veterans with epilepsy who were taking antiepileptic drugs (AEDs) long term can prevent the loss of bone mass (BMD, bone mineral density) associated with AED use compared to patients who were treated with a placebo plus calcium and vitamin D. As a secondary end point we studied the incidence of new morphometric vertebral and nonvertebral fractures. Methods: Antiepileptic drug and osteoporosis prevention trial (ADOPT) was designed as a prospective 2‐year double‐blind, randomized placebo controlled study involving 80 male veterans with epilepsy who were being treated with AEDs such as phenytoin, phenobarbital, sodium valproate, or carbamazepine for a minimum of 2 years. All enrolled participants received calcium and vitamin D supplementation, and were randomized to risedronate or matching placebo. Total body, bilateral proximal femora, and anteroposterior (AP) lumbar spine BMDs in addition to morphometric lateral vertebral assessments (LVAs) were evaluated by a dual energy x‐ray absorptiometry (DXA) instrument. Comparisons of BMDs were made between baseline, 1 year, and after 2 years of enrollment in the study. The incidence of new vertebral and nonvertebral fractures was secondary end point. Key Findings: Of the 80 patients initially enrolled in the study, 53 patients completed the study. Baseline characteristics of the two groups were similar. At the end of the study, in the placebo plus calcium and vitamin D group, we observed a significant improvement in BMD at any of the evaluated sites when compared to their baseline scans in 69% (18/26) of the participants. In the risedronate plus calcium and vitamin D group, we observed significant improvement of BMDs in 70% (19/27) of the participants. At the end of the study, the risedronate group experienced a significant increase of BMD at the lumbar spine L1‐4 (1.267–1.332 g/cm 2 ), which was significantly larger than that seen in the placebo group) (1.229 g/cm 2 vs. 1.245 g/cm 2 ; p = 0.0066).There were nonsignificant differences between the two groups regarding changes of total body BMD or at the proximal bilateral femora. Five new vertebral fractures and one nonvertebral fracture were observed only in the placebo group. Significance: Calcium and vitamin D supplementation or calcium and vitamin D supplementation in addition to risedronate improved BMD in more than 69% of male veterans with epilepsy who were taking AEDs. In the group receiving risedronate plus calcium and vitamin D there was a significant improvement of BMD at the lumbar spine as compared to the placebo group, which also received calcium and vitamin D. The use of risedronate plus calcium and vitamin D prevented the incidence of new vertebral fractures and one nonvertebral fracture in this cohort.